Myocarditis triggers inflammatory response in cardiac fibroblasts and profibrotic activation of myeloid and endothelial cells in mouse model of experimental autoimmune myocarditis. (25th November 2020) - Tkacz, K; Dzialo, E; Weglarczyk, K; Czepiel, M; Siedlar, M; Kania, G; Blyszczuk, P
Abstract: Background/Introduction: Myocarditis, a heart-specific inflammation, is a common cause of pathological tissue remodeling and cardiac fibrosis resulting in stiffening of ventricles, functional impairment and heart failure. Immunization of susceptible mice with alpha myosin heavy chain (αMyHC) and complete Freund's adjuvant (CFA) induces CD4+ T cell-mediated experimental autoimmune myocarditis (EAM). In EAM model, resolution of acute cardiac inflammation is followed by a progressive dilated cardiomyopathy and systolic dysfunction. Purpose: The aim of our study was to identify the role of resident cardiac fibroblasts, cardiac endothelial as well as inflammatory myeloid cells during the course of EAM. Methods: EAM was induced by immunization with αMyHC/CFA in reporter BALB/c mice expressing EGFP under collagen type I promoter (Coll-EGFP) and RFP under a control of α-smooth muscle actin (αSMA) promoter (αSMA-RFP). Using flow cytometry analysis, cardiac cells were phenotyped and quantified at inflammatory (d19–21) and fibrotic (d40) stage of EAM. Sorted EGFP-positive cardiac fibroblasts obtained from healthy and myocarditis-positive mice (day 21 of EAM) were comparatively analyzed for the whole genome transcriptomics using the Next Generation Sequencing with read length 2x150bp and 20–30 million reads per sample. Results: A massive infiltration of inflammatory CD45+CD11b+ myeloid cells (mainly CD11b+CD36+ macrophages, CD11b+CD36–Ly6GhiLy6chi neutrophils, CD11b+CD36–Ly6G–Ly6c– monocytes, CD11b+CD36–Ly6G–Ly6chi inflammatory monocytes) was observed at day 21 of EAM. Myeloid cells as well as endothelial cells showed increased production of type I collagen at day 21, which was further reduced at day 40 of EAM. At day 21, collagen-producing endothelial cells showed particularly elevated levels of adhesion molecules ICAM and VCAM. On the other hand, the total number of EGFP-positive cardiac fibroblasts remained unchanged during the course of EAM, as well as the percentage of cardiac fibroblasts positive for αSMA (myofibroblasts). Gene ontology analysis of transcripts differentially regulated in cardiac fibroblasts during acute myocarditis pointed mainly to activation of immune processes, response to stress, cytoskeletal and extracellular matrix organization. Specifically, in EAM at day 21 cardiac fibroblasts increased transcription of chemokines (Ccl6, Ccl9, Cxcl2, Cxcl3, Cxcl5, Cxcl9, Cxcl13), collagens (Col6a4, Col6a5, Col9a1, Col9a3, Col11a2, Col12a1, Col24a1, Col28a1), and genes involved in ECM biology (Bmp7, Kng2, Lgals3, Cthrc1, Cela1, Spn). Conclusions: In EAM model, inflammatory myeloid and cardiac endothelial cells seem to contribute to excessive collagen type I production, whereas cardiac fibroblasts actively participate in inflammatory and profibrotic responses. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The National Science Centre (Poland)